Arthroscopic Fixation for Acute Acromioclavicular Joint Disruption Using the TightRope Device - Deepak Chaudhary; Vineet Jain; Deepak Joshi; Jitesh Kumar Jain; Ankit Goyal; Nitin Mehta (Journal of Orthopaedic Surgery, 2015)
Purpose. To review outcome after arthroscopic fixation for acute acromioclavicular (AC) joint dislocation using the TightRope device. Methods. Records of 15 men and 2 women aged 19 to 52 (mean, 35) years who underwent arthroscopic fixation using the TightRope device for acute (<3 weeks) AC joint dislocation of Rockwood type III (n=6), type IV (n=1), and type V (n=10) were reviewed. Outcome was evaluated using the Constant score. The coracoclavicular (CC) distance before and after surgery was compared. Results. The mean follow-up period was 22.1 (range, 12–37) months. The mean time to return to work was 4 (range, 1.5–12) months, excluding one failure. The mean postoperative Constant score was 86.4 (range, 63–96). The CC distance decreased from 21.5±5.2 mm preoperatively to 9.8±3.5 mm at 6 months and to 10±3.2 mm at one year. There was no over-correction. All patients had satisfactory outcome except for one who had rupture of the TightRope suture at 6 months. Two patients had partial loss of reduction (≥2 mm) after 3 to 6 months secondary to osteolysis at the clavicular button site. Conclusion. Arthroscopic fixation using the TightRope device for acute AC joint dislocation achieves satisfactory outcome.